Routledge handbook of ethnic conflict - Cordell, Karl 1956-; Wolff, Stefan (Routledge handbooks, 2010)
A global survey of the interaction of race, ethnicity, nationalism and politics. It offers a 360-degree perspective on ethnic conflict: from the theoretical foundations of nationalism and ethnicity, to the causes and consequences of ethnic conflict, and to the various strategies adopted in response to it.